Genetic susceptibility testing and readiness to control weight: Results from a randomized controlled trial. (17th December 2014) - Meisel, Susanne F.; Beeken, Rebecca J.; van Jaarsveld, Cornelia H. M.; Wardle, Jane
<x xml:space="preserve">Abstract</x> Objective To test the hypothesis that adding obesity gene feedback (FTO) to simple weight control advice at a life stage with raised risk of weight gain (university) increases readiness to control weight. Methods Individually randomized controlled trial comparing the effect of: (i) simple weight control advice plus FTO feedback (FA) and (ii) simple weight control advice only (AO) on readiness to engage with weight control. Differences in stage of change by genotype and differential weight control behaviors were secondary outcomes. Results Of 1, 016 participants randomized, only 279 completed follow‐up, yielding 90% power to detect a small effect for readiness to control weight. As predicted, FA participants were more likely to be in the contemplation stage than AO participants (P = 0.023). Participants receiving higher‐risk genetic results were at a higher stage of change than controls (P = 0.003), with a trend toward a higher stage of change than those getting lower‐risk results (P = 0.051). Lower‐risk results did not decrease weight control intentions compared with controls (P = 0.55). There were no group differences in adherence to recommended weight control behaviors (P = 0.87). Conclusions Adding FTO feedback to weight control advice enhanced readiness to control weight, without evidence for genetic determinism, but had no more effect on behavior than weight control advice alone.